Reliability and accuracy of cone-beam computed tomography voxel density and linear distance measurement at different voxel sizes: A study on sheep head cadaver - Enes Güngör; Mehmet Sinan Doğan (Elsevier, 2017)
Background/purpose: The reliability and accuracy of linear distance and voxel density (VD) measurements are very important in dentistry. The purpose of this study was to assess the accuracy and reliability of linear distances and VD measurements of cone-beam computed tomography (CBCT) at different voxel sizes. Materials and methods: Eighteen-millimeter linears of size 40 gutta-percha were prepared in fresh sheep head. The head was scanned using CBCT with 0.25, 0.3, and 0.40 voxel sizes. Standard linear distances of gutta-percha were measured in panoramic CBCT images at 0.25, 0.3, and 0.4 voxel sizes. VD measurements were made separately on spongeous bone of palatal surfaces of the roots of teeth 4, 5, and 6 of maxilla and on cortical bone of teeth 4, 5, and 6 regions of the left and right hemimandibles through cross-sectional imaging. Results: We found that linear distance measurements on panoramic image of CBCT were slightly lower than physical measurements. A significant difference was not found for the gutta-percha linear distances and cortical VD measurements at different voxel sizes (P ≥ 0.05). The correlation between measurements of VD at different voxels in cortical bone was greater than 0.85 (P = 0.000). Conclusion: Linear distance measurements on the sheep head cadaver of 0.25, 0.3, and 0.4 voxel sizes were similar and reliable when compared with physical measurements. In minimizing radiation exposure, VD measurement of cortical bone at 0.4 voxel-based CBCT could be used to estimate cortical bone density. However, studies should be performed on the human head cadaver.